Time and spatially resolved electron spin detection in semiconductor heterostructures by magneto-optical Kerr microscopy - Henn, Tobias; Kießling, Tobias; Molenkamp, Laurens W.; Reuter, Dirk; Wieck, Andreas D.; Biermann, Klaus; Santos, Paulo V.; Ossau, Wolfgang (physica status solidi (b))

Non-polar GaN quantum dots integrated into high quality cubic AlN microdisks - Bürger, M.; Callsen, G.; Kure, T.; Hoffmann, A.; Pawlis, A.; Reuter, Dirk; As, D. J. (physica status solidi (c))

Analysis Method of Tool Topography Change and Identification of Wear Indicators for Heavy Copper Wire Wedge Bonding - Eichwald, Paul; Sextro, Walter; Althof, Simon; Eacock, Florian; Unger, Andreas; Meyer, Tobias; Guth, Karsten (Proceedings of the 47th International Symposium on Microelectronics)
Wire bonding is the most common technology for connecting electronic components. Due to their efficiency bond interconnections made of copper wire are used for example in the aerospace and medical technology as well as in the fields of renewable energies. One of the main cost factors in the manufacturing process is the consumables like bonding tools. The technological transition to copper as wire material causes significant wear on the millimeter large effective contact area of the bonding tool. This wear leads to a loss by a factor of 30 of the number of reliable interconnections which can be produced by a single tool. To reduce setting-up time in the production and minimizing costs, an enlarged bonding tool lifetime is desirable. Consequently a better understanding of wear and recognition of wear pattern is required. Therefore, the paper presents an analyzing method of the tool topography change of a heavy wire bonding tool by using a confocal microscope. Furthermore, the paper discusses the identification of the main wear indicators by the help of the named topography change for different bond parameters, like ultrasonic power and tool geometry. Reference topography has been carried out by choosing typical parameters of the production line. To judge whether the quality requirement of the bond connections made by a single tool cannot be fulfilled shear test of the source bond have been carried out after a defined number of produced bond connections. Main steps of analysis: (I)Topography of the tool surface is sampled after a defined number of bonds by means of a confocal microscope to detect the wear progress.(II)The recorded data is filtered using Matlab. So, measurement errors can be eliminated and the topography can be overlaid more easy to identify differences between diverse tools or differences in wear stages of the same tool.(III)The subsequent discretization of the topography into sub volumes allows to (IV)describe the loss of volume depending on the position in the groove. Thereby, intermediate status of wear of one tool can be used to obtain a persistent description of the topography change over the number of produced bonds by interpolating the confocal data. Afterwards the persistent change of the groove flank has been analyzed for the named test series to identify the main wear indicators and their effect on shear forces. All worn tools show dominant areas for volume loss especially for plastic deformation and accordingly abrasion. These wear mechanism can be referred to the change of main parts of the groove geometry like the rounding of the front and back radius. The most volume loss was identified in the upper part of the tool flanks or rather at the transition from the groove flank to the front or back radius. Furthermore the observation of the center of the groove flank shows just a little change in volume. All in all, the identification of the wear indicators will be discussed with the objective of increasing the tool lifetime by optimizing the tool geometry without losses in bond quality and reliability.
Keywords: wedge/wedge bonding; copper wire; tool wear

Cubic GaN/AlN multi-quantum wells grown on pre-patterned 3C-SiC/Si (001) - Kemper, R. M.; Mietze, C.; Hiller, L.; Stauden, T.; Pezoldt, J.; Meertens, D.; Luysberg, M.; As, D. J.; Lindner, Jörg (physica status solidi (c))
We report for the first time on the growth of cubic AlN/GaN multi‐quantum wells (MQWs) on pre‐patterned 3C‐SiC/Si (001) substrates. The sample structure consists of 10 periods of 2 nm c‐AlN barriers with a 4 nm c‐GaN layer in between, which were grown on 3C‐SiC post shaped structures by means of molecular beam epitaxy. Substrate patterning has been realized by electron beam lithography and a reactive ion etching process. The 3C‐SiC posts have a length of about 550 nm and a height of about 700 nm. (Scanning) transmission electron microscopy studies show that the morphology of the MQWs is clearly influenced by {111} stacking faults, modulating the local growth rate. Further, the growth at the edges of the surface pattern is investigated. The MQW layers cover the 90° edges by developing low‐index facets rather than by forming a conformal system of 90° angled layers.

Self-organized fabrication of periodic arrays of vertical, ultra-thin nanopillars on GaAs surfaces - Riedl, Thomas; Lindner, Jörg (physica status solidi (a))
This paper presents a low‐cost procedure that allows for self‐organized fabrication of periodically arranged, sub‐50 nm diameter, vertical‐sidewall GaAs nanopillars on GaAs surfaces based on nanosphere lithography, and reactive ion etching (RIE). Monodispersed polystyrene (PS) sphere double layers are deposited from a colloidal suspension on pre‐treated, hydrophilized GaAs substrates. Ni is thermally evaporated to act as a hard mask for subsequent RIE. Scanning electron microscopy reveals that the Ni nanoparticles left on the substrate after PS sphere removal have polygon‐shaped in‐plane cross‐sections corresponding to the shape of the double layer mask openings. RIE using SiCl4 at low pressure and high power density leads to the formation of vertical nanopillars with circular to oval cross‐sections, whose diameters are reduced by ∼1/3 compared to those of the Ni nanoparticles. These findings can be explained by plasma‐enhanced surface diffusion and sputtering processes during RIE. The obtained GaAs nanopillars have an average diameter of only ∼23 nm, exhibit an excellent verticality with a sidewall angle of 88.9 ± 0.4° and planar top faces, as visible in transmission electron microscopy images.

Individuation in Adults’ Family Interactions: An Observational Study - Buhl, Heike M.; Scholwin, Berit; Noack, Peter (Journal of Adult Development)
The study investigates the status of individuation in adult child–parent relationships expressed in verbal interactions, as well as considering verbal behavior as a means to individuate. A sample of 41 German adult children aged 20–45 years and their 39 mothers and 19 fathers were videotaped in dyadic conflict discourse. The interactions were coded in their entirety, and scales were allocated to the factor connectedness, individuality, and conflict. Group comparisons show that mothers and fathers do not differ. Middle-aged adults interacted in a more individuated manner than young adults. Their mothers interacted in a way that was more connected and less conflictual than mothers in interactions with younger adults; their fathers, on the other hand, interacted more conflictual. The behavior of adult children and their parents did not differ and so expressed a high amount of behavioral symmetry. Associations between the self-report about the relationship and family members’ behavior point to verbal interaction as a means for negotiating the relationship.
Keywords: Life-span and Life-course Studies; Developmental and Educational Psychology; Experimental and Cognitive Psychology

Does Financial Statement Audit Reduce the Cost of Debt of Private Firms? - Koren, Jernej; Kosi, Urska; Valentincic, Aljosa (SSRN Electronic Journal)
This study examines the effect of audit on private firms’ cost of debt. We use a sample of 1,949 small private firms operating in the period 2006-2010 with optional financial statement audit. High quality data allows us to construct a more precise interest rate measure than existing studies employ. After controlling for obvious sources of demand for voluntary audits (ownership complexity, subsidiary status, bank relations), we find a robust central result that voluntary audits increase rather than decrease the cost of debt financing, contrary to several existing studies. This finding indicates that voluntary audits are generally treated as “adopting a label” and penalised by creditors, regardless of the perceived auditor quality as a result of the lemon problem in the audit market. Even Big-4 audits increase the cost of debt, likely as a result due to the lemon problem in the audit market, although the increase is smaller than for non-Big-4 audits. The results are sensitive to the estimation method used (OLS, Heckman’s two-step, PSM) and (sub-)sample selection. We show that disregarding the underlying assumptions of these estimation methods may lead to incorrect inferences. Additional analyses show that audited firms’ reported earnings are less informative about future operating performance than earnings of their unaudited counterparts. Our results also indicate that results are sensitive to cost of debt definition and this might have affected the results reported in the existing literature.

Physical Activity in Different Preschool Settings: An Exploratory Study - Röttger, K.; Grimminger-Seidensticker, Elke; Kreuser, F.; Assländer, L.; Gollhofer, A.; Korsten-Reck, U.; Gollhofer, A. (Journal of Obesity)
Introduction . Physical activity (PA) in preschoolers is vital to protect against obesity but is influenced by different early-life factors. The present study investigated the impact of different preschool programs and selected family factors on preschoolers’ PA in different countries in an explorative way. Methods . The PA of 114 children (age = 5.3 ± 0.65 years) attending different preschool settings in four cities of the trinational Upper Rhine region (Freiburg, Landau/Germany, Basel/Switzerland, and Strasbourg/France) was measured by direct accelerometry. Anthropometrical and family-related data were obtained. Timetables of preschools were analyzed. Results . Comparing the preschool settings, children from Strasbourg and Landau were significantly more passive than children from Basel and Freiburg (P<.01). With regard to the family context as an important early-life factor, a higher number of children in a family along with the mother’s and child’s anthropometrical status are predictors of engagement in PA. Conclusion . More open preschool systems such as those in Basel, Freiburg, and Landau do not lead to more PA “per se” compared to the highly regimented desk-based system in France. Preliminaries such as special training and the number of caregivers might be necessary elements to enhance PA. In family contexts, targeted PA interventions for special groups should be more focused in the future.

Are we on track with sustainability literacy? - Hahn, Rüdiger; Reimsbach, Daniel (Journal of Global Responsibility)
Purpose – In this viewpoint, the authors aim to discuss sustainability issues in university education. Balancing what we call the “Accounting View” and the “Sustainability View”, the authors illuminate the status of value relevance of sustainability information and question the depth of business students' processing of this information. Design/methodology/approach – The discussion was triggered by an experimental study on sustainability disclosure which revealed interesting findings related to the participating students' prior sustainability and accounting coursework. The authors start the viewpoint from these findings and contrast them with existing views on sustainability and accounting (education). Findings – The amount of accounting coursework was positively related to the probability of including sustainability information in future stock value estimates, whereas this applied only marginally to sustainability coursework. However, students with more sophisticated sustainability knowledge seemed to scrutinize the given sustainability information more deeply, while students with “pure” accounting knowledge seemed more willing to simply accept the information. Practical implications – The authors argue for advancements in the curriculum for business students that foster critical thinking and might prevent students (and thus potential future managers) from using sustainability information superficially. The authors caution against regarding sustainability issues as an “add-on” to existing courses and curricula and call for a combination of integrating sustainability issues in (core) business courses and offering standalone courses on sustainability management or CSR. Originality/value – Triggered by findings from an experimental study, the authors contrast different opinions on sustainability education of business students and offer a new viewpoint on the (supposed) value relevance of sustainability information for future business leaders.
Keywords: Business and International Management

How Profound Is the Allure of Endowed Status in Hierarchical Loyalty Programs? - Eggert, A.; Garnefeld, I.; Steinhoff, Lena (Customer & Service Systems, Special Issue: Customer Empowerment, 1 (1))

Changes in dietary intake during puberty and their determinants: results from the GINIplus birth cohort study - Harris, Carla; Flexeder, Claudia; Thiering, Elisabeth; Buyken, Anette; Berdel, Dietrich; Koletzko, Sibylle; Bauer, Carl-Peter; Brüske, Irene; Koletzko, Berthold; Standl, Marie (BMC Public Health)
Background Understanding changes in dietary intake during puberty could aid the mapping of dietary interventions for primary prevention. The present study describes dietary changes from childhood to adolescence, and their associations with parental education, family income, child education, body mass index (BMI), pubertal onset and screen-time sedentary behaviour. Methods Dietary data (n = 1232) were obtained from food frequency questionnaires at the 10- and 15-year follow-ups of the GINIplus birth cohort study. Intakes of 17 food groups, macronutrients and antioxidant vitamins, were described by a) paired Wilcoxon rank sum tests, comparing average intakes at each time-point, and b) Cohen’s kappa “tracking” coefficients, measuring stability of intakes (maintenance of relative tertile positions across time). Further, associations of changes (tertile position increase or decrease vs. tracking) with parental education, family income, child education, pubertal onset, BMI, and screen-time, were assessed by logistic regression and multinomial logistic regression models stratified by baseline intake tertile. Results Both sexes increased average intakes of water and decreased starchy vegetables, margarine and dairy. Females decreased meat and retinol intakes and increased vegetables, grains, oils and tea. Males decreased fruit and carbohydrates and increased average intakes of meat, caloric drinks, water, protein, fat, polyunsaturated fatty acids (PUFAs), vitamin C and alpha-tocopherol. Both sexes presented mainly “fair” tracking levels [κw = 0.21–0.40]. Females with high (vs. low) parental education were more likely to increase their nut intake [OR = 3.8; 95 % CI = (1.7;8.8)], and less likely to decrease vitamin C intakes [0.2 (0.1;0.5)], while males were less likely to increase egg consumption [0.2 (0.1;0.5)] and n3 PUFAs [0.2 (0.1;0.5)]. Females with a higher (vs. low) family income were more likely to maintain medium wholegrain intakes [0.2 (0.1;0.7) for decrease vs. tracking, and 0.1 (0.0;0.5) for increase vs. tracking], and were less likely to decrease vitamin C intakes [0.2 (0.1;0.6)]. Males with high education were less likely to increase sugar-sweetened foods [0.1 (0.1;0.4)]. Finally, BMI in females was negatively associated with decreasing protein intakes [0.7 (0.6;0.9)]. In males BMI was positively associated with increasing margarine [1.4 (1.1;1.6)] and vitamin C intakes [1.4 (1.1;1.6)], and negatively associated with increasing n3 PUFA. Conclusions Average dietary intakes changed significantly, despite fair tracking levels, suggesting the presence of trends in dietary behaviour during puberty. Family income and parental education predominantly influenced intake changes. Our results support the rationale for dietary interventions targeting children, and suggest that sex-specific subpopulations, e.g. low socio-economic status, should be considered for added impact.
Keywords: Puberty; Dietary intake; Dietary changes; Tracking; Determinants; Epidemiology

Managing Geospatial Linked Data in the GeoKnow Project - Lehmann, Jens; Athanasiou, Spiros; Both, Andreas; García-Rojas, Alejandra; Giannopoulos, Giorgos; Hladky, Daniel; Jay Le Grange, Jon; Ngonga Ngomo, Axel-Cyrille; Ahmed Sherif, Mohamed; Stadler, Claus; Wauer, Matthias; Westphal, Patrick; et al. (The Semantic Web in Earth and Space Science. Current Status and Future Directions)

Fatty acid supply with complementary foods and LC-PUFA status in healthy infants: results of a randomised controlled trial - Libuda, Lars; Mesch, Christina M.; Stimming, Madlen; Demmelmair, Hans; Koletzko, Berthold; Warschburger, Petra; Blanke, Katharina; Reischl, Eva; Kalhoff, Hermann; Kersting, Mathilde (European Journal of Nutrition)

Interactions in IS Project Portfolio Selection: Status Quo and Perspective - Müller, M.; Meier, Christian; Kundisch, Dennis; Zimmermann, Steffen (Wirtschaftsinformatik Proceedings)

“…and they are really lying”: Clean Evidence on the Pervasiveness of Cheating in Professional Contexts from a Field Experiment. - Fahr, Rene; Mir Djawadi, Behnud (Journal of Economic Psychology)
We investigate the pervasiveness of lying in professional contexts such as insurance fraud, tax evasion and untrue job applications. We argue that lying in professional contexts share three characterizing features: (1) the gain from the dishonest behavior is uncertain, (2) the harm that lying may cause to the other party is only indirect and (3) lies are more indirect lies by action or written statements. Conducted as a field experiment with a heterogenous group of participants during a University ‘‘Open House Day’’, our ‘‘gumball-machineexperiment’’ provides field evidence on how preferences for lying are shaped in situations typically found in professional contexts which we consider to be particularly prone to lying behavior compared to other contexts. As a key innovation, our experimental design allows measuring exact levels of cheating behavior under anonymous conditions. We find clean evidence that cheating is prevalent across all sub groups and that more than 32% of the population cheats for their own gain. However, an analysis of the cheating rates with respect to highest educational degree and professional status reveals that students cheat more than non-students. This finding warrants a careful interpretation of generalizing laboratory findings with student subjects about the prevalence of cheating in the population.

Spatially indirect transitions in electric field tunable quantum dot diodes - Rai, Ashish K.; Gordon, Simon; Ludwig, Arne; Wieck, Andreas D.; Zrenner, Artur; Reuter, Dirk (physica status solidi (b))

Managing the bright and dark sides of status endowment in hierarchical loyalty programs - Eggert, Andreas; Steinhoff, Lena; Garnefeld, Ina (Journal of Service Research)

Investigation of cubic GaN quantum dots grown by the Stranski-Krastanov process - Bürger, M.; Lindner, Jörg; Reuter, Dirk; As, D. J. (physica status solidi (c))
We investigate the formation of cubic GaN quantum dots (QDs) on pseudomorphic strained cubic AlN layers on 3C-SiC (001) substrates grown by means of molecular beam epitaxy. Surface morphologies of various QD sizes and densities were obtained from uncapped samples by atomic force microscopy. These results were correlated with similar but capped samples by photoluminescence experiments. The QD density varies by one order of magnitude from ~1x10^10 cm^-2 to ~1x10^11 cm^-2 as a function of the GaN coverage on the surface. The initial layer thickness for the creation of cubic GaN QDs on cubic AlN was obtained to 1.95 monolayers by a comparison between the experimental results and an analytical model. Our results reveal the strain-driven Stranski-Krastanov growth mode as the main formation process of the cubic GaN QDs.

STEM-CL investigations on the influence of stacking faults on the optical emission of cubic GaN epilayers and cubic GaN/AlN multi-quantum wells - Kemper, R. M.; Veit, P.; Mietze, C.; Dempewolf, A.; Wecker, T.; Bertram, F.; Christen, J.; Lindner, Jörg; As, D. J. (physica status solidi (c))
We report the influence of {111} stacking faults on the cathodoluminescence (CL) emission characteristics of cubic GaN (c-GaN) films and cubic GaN/AlN multiquantum wells. Transmission electron microscopy (TEM) measurements indicate that stacking faults (SFs) on the {111} planes are the predominant crystallographic defects in epitaxial films, which were grown on 3CSiC/ Si (001) substrates by plasma-assisted molecular beam epitaxy. The correlation of the SFs and the luminescence output is evidenced with a CL setup integrated in a scanning TEM (STEM). By comparing the STEM images and the simultaneously measured CL signals it is demonstrated that SFs in these films lead to a reduced CL emission intensity. Furthermore, the CL emission intensity is shown to increase with increasing film thickness and decreasing SF density. This correlation can be connected to the reduction of the full width at half maximum of X-ray diffraction rocking curves with increasing film thickness of c-GaN films.

Spatially indirect transitions in electric field tunable quantum dot diodes - Rai, Ashish K.; Gordon, Simon; Ludwig, Arne; Wieck, Andreas D.; Zrenner, Artur; Reuter, Dirk (physica status solidi (b))
We analyse an InAs/GaAs-based electric ﬁeld tunable single quantum dot diode with a thin tunnelling barrier between a buried n þ -back contact and a quantum dot layer. In voltage- dependent photoluminescence measurements, we observe rich signatures from spatially direct and indirect transitions from the wetting layer and from a single quantum dot. By analysing the Stark effect, we show that the indirect transitions result from a recombination between conﬁned holes in the wetting or quantum dot layer with electrons from the edge of the Fermi sea in the back contact. Using a 17 nm tunnel barrier which provides comparably weak tunnel coupling allowed us to observe clear signatures of direct and corresponding indirect lines for a series of neutral and positively charged quantum dot states.
Keywords: excitons; GaAs; InAs; quantum dots; spatially indirect transitions; Stark shift

Praktikabilität des Adjusted Winner Verfahrens bei variablem Status Quo- Punkt und exogenen Einflüssen - Streck, Thomas

Managing the Bright and Dark Sides of Status Endowment in Hierarchical Loyalty Programs - Eggert, Andreas; Steinhoff, Lena; Garnefeld, Ina (Journal of Service Research)
In service industries, hierarchical loyalty programs are common relationship marketing instruments that award elevated status to customers who exceed a certain spending level (e.g., gold membership). In practice, service companies offer elevated status to some customers who do not meet the required spending level, in an attempt to profit from the profound allure of status. Relying on social psychology research and a mixed-method approach, this study analyzes the loyalty impact of status endowments, defined as awards of elevated status to customers who are not entitled to it. An exploratory qualitative study identifies customer gratitude and customer skepticism as positive and negative mediators, respectively, of customers’ attitudinal responses to endowed status. Quantitative studies—two experimental and one survey—substantiate these bright and dark sides of endowed status. The efficacy of status endowment is contingent on the context. To alleviate the dark-side effect, managers can allow target customers to actively choose whether to be endowed, especially those who are close to achieving the status already, and provide valuable preferential treatment to customers elevated by either endowment or achievement. These insights offer guidelines for whether and how to use status endowment in hierarchical loyalty programs.
Keywords: Organizational Behavior and Human Resource Management; Sociology and Political Science; Information Systems

Managing Geospatial Linked Data in the GeoKnow Project - Lehmann, Jens; Athanasiou, Spiros; Both, Andreas; Garcia-Rojas, Alejandra; Giannopoulos, Giorgos; Hladky, Daniel; Hoeffner, Konrad; Jay Le Grange, Jon; Ngonga Ngomo, Axel-Cyrille; Sherif, Mohamed; Stadler, Claus; Wauer, Matthias; et al. (The Semantic Web in Earth and Space Science. Current Status and Future Directions)
Keywords: 2015 group_aksw sys:relevantFor:infai sys:relevantFor:bis sys:relevantFor:geoknow lehmann ngonga MOLE sherif simba dice hoeffner geoknow wauer westphal

Managing the Bright and Dark Sides of Status Endowment in Hierarchical Loyalty Programs - Eggert, A.; Steinhoff, Lena; Garnefeld, I. (Journal of Service Research)

Several Influences during Examinations of Laser Transmission Welding - Current Status - Schöppner, Volker; Fiebig, I.; Lakemeyer, P.; Bates, P.; Zazoum, B.; Zak, G.; DuQuesnay, D. (69th Annual Assembly of the International Institute of Welding (IIW))

Goals as Reference Points: Empirical Evidence from a Virtual Reward System - von Rechenberg, Tobias; Gutt, Dominik; Kundisch, Dennis (Decision Analysis)
Heath et al. (1999) propose a prospect theory model for goal behavior. Their analytical model is based on the assumption that goals inherit the main properties of the prospect theory value function, i.e., reference point dependence, loss aversion, and diminishing sensitivity. We investigate whether these main properties transfer to goal behavior in the field. We take user activity data from a gamified Question & Answer community and analyze how users adjust their contribution behavior in the days surrounding goal achievement, where goals are represented by badges. We find that users gradually increase their performance in the days prior to earning a badge, with performance peaking on the day of the promotion. In subsequent days, user performance gradually diminishes again, with the decline being strongest on the day immediately following the badge achievement. These findings reflect the characteristic S-shape of the prospect theory value function which is convex below the reference point and concave above it. Employing the target-based approach, we can interpret the value function as a cumulative density function of a unimodal probability distribution. Our results suggest that it is more likely that active members of the community focus on the next badge relative to the status already achieved, as their next goal and are less likely to focus on more remote (higher-ranked) badges. Our results thus support the transferability of the main properties of the prospect theory value function to goal behavior in the field and suggest a distinct shape of the value function around goals.

Heat flow, transport and fluctuations in etched semiconductor quantum wire structures - Riha, Christian; Chiatti, Olivio; Buchholz, Sven S.; Reuter, Dirk; Wieck, Andreas D.; Fischer, Saskia F. (physica status solidi (a))

LiTaO3 phonon dispersion and ferroelectric transition calculated from first principles - Friedrich, Michael; Schindlmayr, Arno; Schmidt, Wolf Gero; Sanna, Simone (Physica Status Solidi B)
The phonon dispersions of the ferro‐ and paraelectric phase of LiTaO3 are calculated within density‐functional perturbation theory. The longitudinal optical phonon modes are theoretically derived and compared with available experimental data. Our results confirm the recent phonon assignment proposed by Margueron et al. [J. Appl. Phys. 111, 104105 (2012)] on the basis of spectroscopical studies. A comparison with the phonon band structure of the related material LiNbO3 shows minor differences that can be traced to the atomic‐mass difference between Ta and Nb. The presence of phonons with imaginary frequencies for the paraelectric phase suggests that it does not correspond to a minimum energy structure, and is compatible with an order‐disorder type phase transition.

Students with Special Educational Needs (SEN) in Learning Disabilities (LD) and Emotional and Behavioural Disorders (EBD) in Rhineland-Palatinate: Social Skills, Behavioural Difficulties and Social Status. - Laubenstein, Désirée; Scheer, D.

Fabrication and characterization of two-dimensional cubic AlN photonic crystal membranes containing zincblende GaN quantum dots - Blumenthal, Sarah; Bürger, Matthias; Hildebrandt, Andre; Förstner, Jens; Weber, Nils; Meier, Cedrik; Reuter, Dirk; As, Donat J. (physica status solidi (c))
We successfully developed a process to fabricate freestanding cubic aluminium nitride (c-AlN) membranes containing cubic gallium nitride (c-GaN) quantum dots (QDs). The samples were grown by plasma assisted molecular beam epitaxy (MBE). To realize the photonic crystal (PhC) membrane we have chosen a triangular array of holes. The array was fabricated by electron beam lithography and several steps of reactive ion etching (RIE) with the help of a hard mask and an undercut of the active layer. The r/a- ratio of 0.35 was deter- mined by numerical simulations to obtain a preferably wide photonic band gap. Micro-photoluminescence (μ-PL) measurements of the photonic crystals, in particular of a H1 and a L3 cavity, and the emission of the QD ensemble were performed to characterize the samples. The PhCs show high quality factors of 4400 for the H1 cavity and about 5000/3000 for two different modes of the L3 cavity, respectively. The energy of the fundamental modes is in good agreement to the numerical simulations.
Keywords: tet_topic_phc; tet_topic_qd

Joint Raman spectroscopy and HRXRD investigation of cubic gallium nitride layers grown on 3C-SiC - Rüsing, Michael; Wecker, T.; Berth, Gerhard; As, Donat Josef; Zrenner, Artur (physica status solidi (b))
Cubic gallium nitride (GaN) films are analyzed with highresolution X-ray diffraction (HRXRD) and Raman spectroscopy. Several cubic GaN layers were grown on 3C-SiC (001) substrate by radio-frequency plasma-assisted molecular beam epitaxy. The layer thickness of the cubic GaN was varied between 75 and 505 nm. The HRXRD analysis reveals a reduction of the full-width at half-maximum (FWHM) of omega scans for growing layer thicknesses, which is caused by a partial compensation of defects. The Raman characterization confirms well-formed c-GaN layers. A more detailed examination of the longitudinal optical mode hints at a correlation of the FWHM of the Raman mode with the dislocation density, which shows the possibility to determine dislocation densities by Ramanspectroscopy on a micrometer scale, which is not possible by HRXRD. Furthermore, this Raman analysis shows that normalized Raman spectra present an alternative way to determine layer thicknesses of thin GaN films.
Keywords: cubic gallium nitride; dislocation density; HRXRD; Raman spectroscopy

Investigating Networks within the field of Higher Organisation Institutions - Jenert, Tobias; Gommers , Luci
Higher education institutions (HEIs) have been described as “loosely coupled systems” (Weick, 1976) where academic disciplines have stronger cohesive forces than formal structures (Becher & Trowler, 2001). Disciplinary ties are also extremely important for the development of teaching practices in HEIs. Roxa & Martensson (2011) have shown that higher education faculty form local networks in which they share and develop teaching-related experiences. These networks are influenced by disciplinary affiliation and mediated by senior faculty (Roxa & Martensson, 2015). Considering these findings, its is not self-evident for the actors on different vertical (e.g. management, faculty and education developers) and horizontal levels (e.g. disciplines) of HEIs to work collaboratively. Therefore, the bounded nature of disciplinary networks can actually inhibit the development of educational innovations that require collaboration beyond such “disciplinary microcultures” (Kries & Nierobisch, 2016). Effective educational practices such as problem-based curricula or cross-disciplinary co-teaching require interactions that reach beyond disciplinary and hierarchical boundaries. In this study we investigate a network – “Lehren” – that was initiated in Germany to stimulate educational innovations in HEIs by overcoming the abovementioned boundaries. A series of five workshops brought together 32 potential innovators representing different disciplines, functions (management, teaching faculty, educational developers), and status groups (full professors, post-docs, others). Three of these workshop series provide a total 96 individuals who are intended to form a professional network promoting educational innovation in their respective HEIs. Providing intense support and incentives to collaborate among each other (network meetings, travel funds, online communities), the aim is to develop a heterogeneous network connecting people with, among others, different functions and from different disciplines.

Correlation of the Carrier Decay Time and Barrier Thickness for Asymmetric Cubic GaN/Al0.64Ga0.36N Double Quantum Wells - Wecker, Tobias; Callsen, Gordon; Hoffmann, Axel; Reuter, Dirk; As, Donat Josef (physica status solidi (b))

Incorporation of germanium for n-type doping of cubic GaN - Deppe, Michael; Gerlach, Jürgen W.; Reuter, Dirk; As, Donat Josef (physica status solidi (b))

Three-Stage Power System Restoration Methodology Considering Renewable Energies - Shen, Cong; Kaufmann, Paul; Braun, Martin (Elsevier International Journal of Electrical Power and Energy Systems (IJEPES))
This is a study of a combined load restoration and generator start-up procedure. The procedure is structured into three stages according to the power system status and the goal of load restoration. Moreover, for each load restoration stage, the proposed algorithm determines a load restoration sequence by considering renewable energy such as solar and wind park to achieve objective functions. The validity and performance of the proposed algorithm is demonstrated through simulations using IEEE-39 network.
Keywords: Load restorationRestoration stageRenewable energyVoltage/frequency fluctuations

Dimensionen inklusionsbezogener Fortbildungsmotivation von Sonderpädagoginnen und Sonderpädagogen und Lehrkräften allgemeiner Schulen - Gorges, Julia; Neumann, Phillip; Lütje-Klose, Birgit; Wild, Elke (Empirische Sonderpädagogik)
In der vorliegenden Studie wird die konzeptuelle Binnenstruktur der Fortbildungsmotivation von Sonderpädagoginnen und Sonderpädagogen und Lehrkräften allgemeiner Schulen (N=287) mit Blick auf eine inklusionsbezogene Fortbildung zur multiprofessionellen Kooperation aus Perspektive der Erwartungs-Wert-Theorie untersucht. Konfirmatorische Faktorenanalysen zeigen eine 4-Komponenten-Struktur des subjektiven Wertes. Teilnahmeförderliche Wertüberzeugungen, die mithilfe von Items mit intrinsischer, utilitaristischer und persönlicher Ausrichtung erfasst wurden, lassen sich nach den Bezugspunkten Inhalt, Status als Teilnehmerin oder Teilnehmer und Abschluss untergliedern. Eine Kostenkomponente mit monetären und nicht-monetären Anteilen bildet einen eigenständigen Faktor. Der 4-faktorielle subjektive Wert lässt sich weiterhin von einem Bilanzwert abgrenzen, der ein Gesamturteil hinsichtlich der untersuchten Fortbildung reflektiert und primär von inhaltsbezogenen Wertkomponenten sowie der Kostenkomponente des Wertes vorhergesagt wird. Es zeigen sich professionsbezogene Unterschiede sowohl bei der Höhe der Werteinschätzungen als auch bei deren Zusammenspiel zur Bestimmung des Bilanzwertes. Die Diskussion thematisiert theoretische und praktische Implikationen der Befunde.
Keywords: Erwartungs-Wert-Theorie; Inklusion; Lehrerfortbildung; Motivation; multiprofessionelle Kooperation; subjektiver Aufgabenwert; BiFoKi

Wann ist eine Unterrichtsplanung 'gut'? - Planungsperformanz in Praxisratgebern zur Unterrichtsplanung - Vogelsang, Christoph; Riese, Josef (Die Unterrichtsplanung: Ein in Vergessenheit geratener Kompetenzbereich?! Status Quo und Perspektiven aus Sicht der empirischen Forschung.)

Unterrichtsplanung im Fach Geschichte – Modellierung und Erfassung geschichtsdidaktischen Planungswissens von Lehramtsstudierenden - Wolf, Jörgen; Seiffert, Joana; Seifert, Andreas; Rothland, Martin; Brauch, Nicola (Die Unterrichtsplanung: Ein in Vergessenheit geratener Kompetenzbereich?! Status und Perspektiven aus der Sicht der empirischen Forschung.)

Shoulda, Coulda, Woulda – Non-Canonical Forms on the Move? - Freudinger, Markus (Zeitschrift für Anglistik und Amerikanistik)
Abstract In this paper, the contractions shoulda, coulda, woulda are compared with their respective full forms should have , would have , and could have . Although the full forms are used much more frequently and are, therefore, considered canonical, the non-canonical forms have increased in frequency throughout the better part of the twentieth century. They are predominantly used in American English – in conversation as well as in fictional writing to imitate speech. With respect to their syntactic environment, shoulda, coulda , and woulda behave differently than their full counterparts since they are often used without subjects and without lexical verbs. Some of these uses can be explained by the fact that shoulda, coulda , and woulda are not always used as verbal items but also as nouns, adjectives, and interjections. Due to their overall low frequency and their restriction to a particular register, however, it appears they will keep their non-canonical status for the foreseeable future.
Keywords: Literature and Literary Theory; Linguistics and Language; Language and Linguistics

Association between full breastfeeding, timing of complementary food introduction, and iron status in infancy in Germany: results of a secondary analysis of a randomized trial - Libuda, Lars; Hilbig, Annett; Berber-Al-Tawil, Seda; Kalhoff, Hermann; Kersting, Mathilde (European Journal of Nutrition)

Not All VANET Broadcasts Are the Same: Context-Aware Class Based Broadcast - Dressler, Falko; Klingler, Florian; Sommer, Christoph; Cohen, Reuven (IEEE/ACM Transactions on Networking)
A major building block of Vehicular Ad Hoc Net- works (VANETs) is broadcasting: the use of wireless communication for sharing information among vehicles, or between vehicles and infrastructure. Dozens of broadcast protocols have been developed in recent years, including protocols for 1-hop broadcasting of vehicle status information (beaconing) and for geocasting-based applications. However, most of these protocols were designed for one application and cannot co-exist, nor can one broadcast solution meet the demands of all applications. These observations motivated our effort to develop a holistic Network layer for VANETs. We identify the need for making VANET broadcast context-aware, and for supporting four different classes of broadcast protocols, each with its own properties. These classes are not only able to co-exist on the same Network layer, but also to complement one another's functionality. Thus, large applications as well as more holistic Transport protocols can be designed by combining two or more broadcast classes. We discuss the specific characteristics of these classes and design candidate protocols for each class.

Business Intelligence & Analytics Cost Accounting: A Survey on the Perceptions of Stakeholders - Grytz, Raphael; Krohn-Grimberghe, Artus (Proceedings of the 51st Hawaii International Conference on System Sciences)
As data driven decision-making using business intelligence and analytics (BI&A) becomes standard in companies, the importance of mitigating the accompanying growth in costs increases. Research shows that increasing transparency to the granularity of individual BI&A artefacts such as reports or analytic applications is a necessary means, but in practice the introduction of said systems is cumbersome and adoption is slow. We address the status quo of BI&A cost accounting for three types of stakeholders: users, developers and managers. The results show in which areas of application a strong need for action exists and we identify major challenges for further research are ahead. Our findings indicate for example that managers at the same time regard cost accounting for BI&A with a higher potential benefit while they also believe they have already established a higher degree of implementation in their enterprises compared to the other stakeholder types. We conclude that BI&A professionals have to consider these different perceptions to run a successful department and gain traction for BI&A cost accounting.

Optical Properties of Cubic GaN Quantum Dots Grown by Molecular Beam Epitaxy - Blumenthal, Sarah; Reuter, Dirk; As, Donat Josef (physica status solidi (b))

Alkalinization with potassium bicarbonate improves glutathione status and protein kinetics in young volunteers during 21-day bed rest - Biolo, Gianni; Di Girolamo, Filippo Giorgio; Heer, Martina; Sturma, Mariella; Mazzucco, Sara; Agostini, Francesco; Situlin, Roberta; Vinci, Pierandrea; Giordano, Mauro; Bühlmeier, Judith; Frings-Meuthen, Petra; Mearelli, Filippo; et al. (Clinical Nutrition)
Keywords: Critical Care and Intensive Care Medicine; Nutrition and Dietetics

Properties of Co‐Evaporated RbInSe 2 Thin Films - Kodalle, Tim; Kormath Madam Raghupathy, Ramya; Bertram, Tobias; Maticiuc, Natalia; Yetkin, Hasan A.; Gunder, René; Schlatmann, Rutger; Kühne, Thomas; Kaufmann, Christian A.; Mirhosseini, S. Hossein (physica status solidi (RRL) – Rapid Research Letters)

Electric Field Induced Raman Scattering at the Sb–InP(110) Interface: The Surface Dipole Contribution - Esser, Norbert; Schmidt, Wolf Gero (physica status solidi (b))

Stacked Self-Assembled Cubic GaN Quantum Dots Grown by Molecular Beam Epitaxy - Blumenthal, Sarah; Rieger, Torsten; Meertens, Doris; Pawlis, Alexander; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
We have investigated the stacking of self-assembled cubic GaN quantum dots (QDs) grown in Stranski–Krastanov (SK) growth mode. The number of stacked layers is varied to compare their optical properties. The growth is in situ controlled by reflection high energy electron diffraction to prove the SK QD growth. Atomic force and transmission electron microscopy show the existence of wetting layer and QDs with a diameter of about 10 nm and a height of about 2 nm. The QDs have a truncated pyramidal form and are vertically aligned in growth direction. Photoluminescence measurements show an increase of the intensity with increasing number of stacked QD layers. Furthermore, a systematic blue-shift of 120 meV is observed with increasing number of stacked QD layers. This blueshift derives from a decrease in the QD height, because the QD height has also been the main confining dimension in our QDs.
Keywords: cubic crystals; GaN; molecular beam epitaxy; quantum dots

Optimization of Cooling Utility System with Continuous Self-Learning Performance Models - Peesel, Ron-Hendrik; Schlosser, Florian; Meschede, Henning; Dunkelberg, Heiko; Walmsley, Timothy (Energies)
Prerequisite for an efficient cooling energy system is the knowledge and optimal combination of different operating conditions of individual compression and free cooling chillers. The performance of cooling systems depends on their part-load performance and their condensing temperature, which are often not continuously measured. Recorded energy data remain unused, and manufacturers’ data differ from the real performance. For this purpose, manufacturer and real data are combined and continuously adapted to form part-load chiller models. This study applied a predictive optimization algorithm to calculate the optimal operating conditions of multiple chillers. A sprinkler tank offers the opportunity to store cold-water for later utilization. This potential is used to show the load shifting potential of the cooling system by using a variable electricity price as an input variable to the optimization. The set points from the optimization have been continuously adjusted throughout a dynamic simulation. A case study of a plastic processing company evaluates different scenarios against the status quo. Applying an optimal chiller sequencing and charging strategy of a sprinkler tank leads to electrical energy savings of up to 43%. Purchasing electricity on the EPEX SPOT market leads to additional costs savings of up to 17%. The total energy savings highly depend on the weather conditions and the prediction horizon.

Assessing causal links between metabolic traits, inflammation and schizophrenia: a univariable and multivariable, bidirectional Mendelian-randomization study - Lin, Bochao D; Alkema, Anne; Peters, Triinu; Zinkstok, Janneke; Libuda, Lars; Hebebrand, Johannes; Antel, Jochen; Hinney, Anke; Cahn, Wiepke; Adan, Roger; Luykx, Jurjen J (International Journal of Epidemiology)
Abstract Background Blood immunoreactive biomarkers, such as C-reactive protein (CRP), and metabolic abnormalities have been associated with schizophrenia. Studies comprehensively and bidirectionally probing possible causal links between such blood constituents and liability to schizophrenia are lacking. Methods To disentangle putative causal links between CRP blood levels and schizophrenia in both directions, we conducted multiple univariable Mendelian-randomization (MR) analyses, ranging from fixed-effect to inverse variance-weighted (IVW), weighted-median, MR Egger and generalized summary-data-based Mendelian-randomization (GSMR) models. To prioritize metabolic risk factors for schizophrenia, a novel multivariable approach was applied: multivariable Mendelian-randomization–Bayesian model averaging (MR-BMA). Results All forward univariable MR analyses consistently showed that CRP has a protective effect on schizophrenia, whereas reverse MR analyses consistently suggested absent causal effects of schizophrenia liability on CRP blood levels. Using MR-BMA, as the top protective factors for schizophrenia we prioritized leucine and as the prime risk-factor triglycerides in medium very-low-density lipoprotein (VLDL). The five best-performing MR-BMA models provided one additional risk factor: triglycerides in large VLDL; and two additional protective factors: citrate and lactate. Conclusions Our results add to a growing body of literature hinting at metabolic changes—in particular of triglycerides—independently of medication status in schizophrenia. We also highlight the absent effects of genetic liability to schizophrenia on CRP levels.

Erfolg versprechende Industrie 4.0-Zielposition - Ermittlung unter Berücksichtigung zukünftiger Umfeldentwicklungen - Pierenkemper, Christoph; Reinhold, Jannik; Dumitrescu, Roman; Gausemeier, Jürgen (Industrie 4.0 Management (5))
Mithilfe von Industrie 4.0-Reifegradmodellen können Unternehmen ihren Leistungsstand im Kontext Industrie 4.0 systematisch erfassen. Mit der Ermittlung des Status Quos ist in aller Regel die Frage verbunden „Wo wollen wir zukünftig hin?“. Vor dem Hintergrund, dass Unternehmen aus unterschiedlichen Gründen nicht immer das grundsätzlich Mögliche einführen können, ist die Beantwortung dieser Frage nicht trivial. Ist sich ein Unternehmen über seine I4.0-Zielposition vermeintlich im Klaren, führen äußere Einflüsse häufig dazu, dass die Zielerreichung erschwert wird, was oftmals eine Anpassung der Zielposition zur Folge hat. Es gilt also, diese Umstände bereits in der Planung zu berücksichtigen. Der vorliegende Beitrag zeigt auf, wie Umfeldentwicklungen bei der Ermittlung einer Erfolg versprechenden I4.0-Zielposition von Unternehmen einbezogen werden können.